Respuesta :
Answer:
[tex]42^{2} -28^{2} =980[/tex]
Step-by-step explanation:
If you evaluate the equation using the factorization method by difference of perfect squares, it would be done as follows
[tex]a^{2} -b^{2} = (a+b)(a-b)[/tex]
Therefore
[tex]42^{2} -28^{2} = (42-28)(42+28)[/tex]
Solving
[tex](14)(70)=980[/tex]
Answer:
None
Step-by-step explanation:
The general form of the difference of perfect squares method is: [tex]a^2-b^2=(a+b)(a-b)[/tex]
Demonstration
The right part of the previous equation could be split like this:
[tex]a^2-b^2=a^2-a\cdot b + a\cdot b - b^2[/tex]
Which can be simplified like this:
[tex]a^2-b^2=a^2-b^2[/tex]
We have obtained the same result
Real problem
According to the problem [tex]42^2 - 28^2[/tex] the development would be:
[tex]42^2 - 28^2=(42+28)\cdot (42-28)[/tex]
The idea is to solve each pair of parenthesis and then to multiply.
[tex]42^2 - 28^2=(70)\cdot (14)=980[/tex]
Thus, the result is not in the options because the problem asks for [tex]42^2 - 28^2[/tex] and the options are related to [tex]42^2 - 38^2[/tex]